Drying of NCM Cathode Electrodes with Porous, Nanostructured Particles Versus Compact Solid Particles: Comparative Study of Binder Migration as a Function of Drying Conditions. Issue 4 (28th January 2022) - Klemens, Julian; Schneider, Luca; Herbst, Eike Christian; Bohn, Nicole; Müller, Marcus; Bauer, Werner; Scharfer, Philip; Schabel, Wilhelm
Abstract : Porous, nanostructured Li(Ni x Co y Mn)O2 (NCM) achieves an improvement in the fast‐charging capability and the durability of lithium‐ion batteries. This improvement is attributed to an extended electrolyte—active material interface, where the electrochemical reactions take place and thus shorter diffusion paths inside the active material particles are necessary for charge transfer. Due to the porous particle morphology, new processing challenges arise compared to compact solid NCM. Herein, the properties of the slurries and the electrodes made of the two active materials and, in particular, the influence of the drying process on the binder distribution, are comparatively investigated. For the same composition of the slurries, a significantly lower dependence of adhesion force and discharge capacity at higher C‐rates on the drying rate is shown when using porous, nanostructured particles instead of solid particles. Binder migration and thus an inhomogeneous concentration distribution of the polyvinylidene fluoride binder is less pronounced for these electrodes during faster drying. Cell tests with half cells show that after increasing the drying rate by more than 350%, the discharge capacity of the electrodes consisting of solid NCM is reduced by about 63% at 5C while for the electrodes made of porous material no reduction is measured. Abstract : Herein, the properties of electrodes made of two different active materials at increasing drying rates and the binder distribution are comparatively investigated. When using porous nanostructured particles instead of solid particles, a significantly lower binder migration and a very low dependence of the discharge capacity at higher C rates on the drying rate are observed.